2002
DOI: 10.1016/s0014-5793(02)03556-1
|View full text |Cite
|
Sign up to set email alerts
|

IRF‐8/ICSBP and IRF‐1 cooperatively stimulate mouse IL‐12 promoter activity in macrophages

Abstract: IRF-8/ICSBP and IRF-1 are IRF family members whose expression is induced in response to IFN-Q Q in macrophages. IL-12 is a cytokine produced in macrophages that plays a critical role in host defense. IFN-Q Q and bacterial lipopolysaccharide (LPS) induce IL-12p40 transcription, which is necessary for the production of IL-12. We have previously shown that IL12p40 expression is impaired in ICSBP-de¢cient mice and that transfection of ICSBP together with IRF-1 can activate IL12p40 expression in mouse macrophage ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
73
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 28 publications
2
73
0
2
Order By: Relevance
“…Furthermore, there may be species-specific differences in the hierarchical importance of these various cis-acting control elements. Two recent papers functionally characterized an ISRE at this location in the IL-12 p40 promoter (37,38). These groups suggest a role for IRF-1 binding to this element.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, there may be species-specific differences in the hierarchical importance of these various cis-acting control elements. Two recent papers functionally characterized an ISRE at this location in the IL-12 p40 promoter (37,38). These groups suggest a role for IRF-1 binding to this element.…”
Section: Discussionmentioning
confidence: 96%
“…IL-12 is a proinflammatory cytokine, and the expression of its two subunits, p40 and p35, are known to be transcriptionally regulated by NF-κB and IRFs (Grumont et al, 2001;Liu et al, 2003;Maruyama et al, 2003;Masumi et al, 2002). Cameron et al found that the inhibition of LPS-induced IL-12 production in L. mexicana amastigote-infected MΦs was due to the degradation of IκB and NF-κB by amastigotes-derived cysteine peptidase B (Cameron et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…IRF-1 and IRF-8/ICSBP can bind to the promoters of mouse IL-12p35 and p40 genes and activate IL-12 expression Maruyama et al, 2003;Masumi et al, 2002). To determine whether La parasite-induced IL-12 suppression correlates with alterations in IRF-1 or IRF-8, we examined the expression of IRF-1 and IRF-8 following La infection.…”
Section: Amazonensis Amastigote Infection Suppresses Irf-1 and Irfmentioning
confidence: 99%
“…The interaction between IRF-8 and IRF-1, both of which are IFN-␥-inducible, together with PU.1, which is an hematopoietic specific factor expressed constitutively in these cells, is a paradigm for the expression of many genes in mature macrophages like the phagocytic oxidase subunits (p67 and gp91) (44), IL-1␤ (45), ISG15 (32), Nramp1 (31), , and IL-12 (47,48). This complex is therefore characteristic of enhanceosomes of many IFN-␥ induced genes in mature macrophages.…”
Section: Discussionmentioning
confidence: 99%